Efek Residu Pemupukan Organik dan Anorganik untuk Pertumbuhan Tanaman Selada (Lactuca sativa L.) pada Tanah Bekas Tsunami - Erida Nurahmi (Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Fertilization Residual Effect Growth on Organic and Inorganic for Lettuce Plant (Lactuca sativa L.) With Used in Tsunami SoilABSTRACT. Remediation of former tsunamis can be made with organic and inorganic fertilizer. Efforts to improve tsunami land using organic ingredients, to create a land that is good for plant growth is by maintaining a balanced plant nutrient availability. This can be done by the way of inorganic fertilizer. Most needed nutrients plants in large numbers and balanced is the elements nitrogen (N), phosphorus (P) and potassium (K) how far the effect of organic and inorganic fertilizers on the growth of lettuce and elemental content of NPK in soil and plant remains problems that need to be tested. The experimental design used in this research is completely randomized design (CRD) 4 x 2 factorial with three replications. There were two factors studied, namely manure doses (K) and NPK fertilizer doses Pearl (M). Increased plant growth and nutrient content of lettuce N, P, and K in soil and plants due to organic and inorganic fertilizer application is highly dependent on the those administered. Fertilizer combinations that produce the best growth of lettuce plant was obtained in combination with organic fertilizer 30 ton ha-1 with the addition of inorganic NPK fertilizer 1000 kg ha-1, particularly in the first planting, and has decreased in the second planting. Residues of organic and inorganic fertilizer application also affected growth and nutrient uptake, but the effect is lower than the effect at the beginning of giving fertilizer.